2015
DOI: 10.1097/md.0000000000001635
|View full text |Cite|
|
Sign up to set email alerts
|

Avoidance of Blood Transfusion to Patients Suffering From Myocardial Injury and Severe Anemia Is Associated With Increased Long-Term Mortality

Abstract: Myocardial injury and anemia are common among patients in internal medicine departments. Nevertheless, the level of anemia in which blood should be given to these patients is ill defined.We conducted a retrospective, cohort analysis.A total of 209 patients hospitalized to internal medicine, with myocardial injury (troponin I > 0.2 mcg/L, not diagnosed as ACS, acute coronary syndrome) and anemia (Hb < 10 g/dL, without overt bleeding) were included. The overall in-hospital mortality rate was 20.7%. A total of 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Hematocrit <30% was included as a predictor for mortality in their model. Barbarova et al [ 20 ] conducted a retrospective cohort analysis of 209 consecutive patients suffering from myocardial injury, with concomitant anemia. In their study, Hb <8 g/dL was found to be an independent risk factor reducing survival in patients not receiving RBC transfusions when compared to transfused patients, whereas no significant difference was observed in patients with Hb ≥8 g/dL between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Hematocrit <30% was included as a predictor for mortality in their model. Barbarova et al [ 20 ] conducted a retrospective cohort analysis of 209 consecutive patients suffering from myocardial injury, with concomitant anemia. In their study, Hb <8 g/dL was found to be an independent risk factor reducing survival in patients not receiving RBC transfusions when compared to transfused patients, whereas no significant difference was observed in patients with Hb ≥8 g/dL between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Shah et al ( 42 ) reported that the risk associated with low levels of hemoglobin is greater in patients with myocardial infarction than for those with stable angina. Therefore, a previous study treated anemic patients with myocardial injury with blood transfusions and demonstrated favorable outcomes ( 44 ). In addition, patients with coronary artery disease are given treatment to maintain their hemoglobin concentrations at a minimum of 100 g/l ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Severe anemia has also been found to relate with mortality in patients with MI and HF (134, 135). Barbarova et al (136) showed that patients with severe anemia and elevated troponin levels presenting to internal medicine departments due to non-cardiac problems had worse long-term survival if they did not get blood transfusion. The main reason of the increase in cTn in case of severe anemia may be resultant tissue hypoxia leading to myocardial injury.…”
Section: Severe Anemiamentioning
confidence: 99%